2018
DOI: 10.1016/j.bbadis.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of AdipoR1 and AdipoR2 in liver fibrosis

Abstract: Activation of the adiponectin (APN) signaling axis retards liver fibrosis. However, understanding of the role of AdipoR1 and AdipoR2 in mediating this response is still rudimentary. Here, we sought to elucidate the APN receptor responsible for limiting liver fibrosis by employing AdipoR1 and AdipoR2 knock-out mice in the carbon tetrachloride (CCl) model of liver fibrosis. In addition, we knocked down receptor function in primary hepatic stellate cells (HSCs) in vitro. Following the development of fibrosis, Adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Hepatic stellate cells (HSC) and Kupffer cells constitutively express the same amount of AdipoR1 and AdipoR2 [ 15 , 16 ]. HSC are activated following a trauma and lead to the secretion of collagen and to the formation of scar tissue, leading to chronic fibrosis or cirrhosis.…”
Section: Adiponectin In Healthy Livermentioning
confidence: 99%
“…Hepatic stellate cells (HSC) and Kupffer cells constitutively express the same amount of AdipoR1 and AdipoR2 [ 15 , 16 ]. HSC are activated following a trauma and lead to the secretion of collagen and to the formation of scar tissue, leading to chronic fibrosis or cirrhosis.…”
Section: Adiponectin In Healthy Livermentioning
confidence: 99%
“…A host of factors contribute to the trans-differentiation of HSCs to mature myofibroblasts, including transforming growth factor (TGF-β), platelet derived growth factor (PDGF-BB), high glucose, and reactive oxygen species (ROS) (Liu and Desai, 2015;Alzahrani et al, 2018;Hou and Syn, 2018;Jia et al, 2018). ROS production, similar to fibrogenesis, is also considered a host defense mechanism (Sies, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have recently demonstrated that adiponectin, a 30 kDa adipocytokine primarily secreted by white adipose tissue (WAT), has anti-fibrotic properties both in vivo and in vitro [610]. Adiponectin signaling occurs via its two cognate receptors: adiponectin receptor 1 and 2 [11,12]. However, the molecular mechanism responsible for anti-fibrotic effects induced by adiponectin remained unexplored.…”
Section: Introductionmentioning
confidence: 99%